Analysis of genetic stability at SSR loci during somatic embryogenesis in maritime pine (Pinus pinaster) - Marum, Liliana (2009)
Somatic embryogenesis (SE) is a propagation tool of particular interest for accelerating the deployment of new high-performance planting stock in multivarietal forestry. However, genetic conformity in in vitro propagated plants should be assessed as early as possible, especially in long-living trees such as conifers. The main objective of this work was to study such conformity based on genetic stability at simple sequence repeat (SSR) loci during somatic embryogenesis in maritime pine (Pinus pinaster Ait.). Embryogenic cell lines (ECLs) subjected to tissue proliferation during 6, 14 or 22 months, as well as emblings regenerated from several ECLs, were analyzed. Genetic variation at seven SSR loci was detected in ECLs under proliferation conditions for all time points, and in 5 out of 52 emblings recovered from somatic embryos. Three of these five emblings showed an abnormal phenotype consisting mainly of plagiotropism and loss of apical dominance. Despite the variation found in somatic embryogenesis-derived plant material, no correlation was established between genetic stability at the analyzed loci and abnormal embling phenotype, present in 64% of the emblings. The use of microsatellites in this work was efficient for monitoring mutation events during the somatic embryogenesis in P. pinaster. These molecular markers should be useful in the implementation of new breeding and deployment strategies for improved trees using SE.